Voltage quality in electrical power systems - Schlabbach, J. (IEE power and energy series ;, 2001)
Problems of voltage quality are becoming increasingly important with the growth in power electronics and the high-sensitivity of electronic equipment. Translated and updated from the German original published by VDE-Verlag, this volume details the theoretical background to low-voltage conducted disturbances in relation to voltage quality. The text describes solutions to practical application problems, including measurement, assessment and countermeasures, set in the context of European standards.